Studi Komparatif Pengaruh Perubahan Tampilan Visual Desain Interior Gerai Coach terhadap Minat Beli Konsumen di Surabaya - Clarissa Monica Gunawan (Intra, 2017)
The development of the retail industry have led to a competitive world where retailers are in need to feature their product and increase selling. One significant method is through the visual appearance of their physical stores’ interior design. “Coach” is one of the luxury handbag international brands with a significant yet interesting visual transformation of the store’s interior design in order to increase selling.This thesis is a comparative research that aims to compare the effects the of visual appearance of “Coach” store interior design, before and after transformation, to the consumer’s buying interest in Surabaya. Results show that the store’s interior design visual appearance does affect the buying interest mostly through the architectural form and interior circulation after transformation. Therefore, the findings of this research supports the notion that an optimalized interior design visual appearance could increase consumer’s buying interest.